2010
DOI: 10.1159/000288638
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences among Patients with a Single Depressive Episode

Abstract: Background: Studies on gender differences in depression have usually included a mixture of patients with first-episode, chronic and recurrent depression. Consequently, the results might be confounded by the history of depression among participants. The present study evaluated gender differences in sociodemographic, clinical and treatment variables among patients suffering exclusively from single-episode depression. Method: Systematic recruitment of 301 participants via the Danish Psychiatric Central Research R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 108 publications
(78 reference statements)
1
8
0
1
Order By: Relevance
“…The gender difference of the original RRS was not apparent in our data. This is consistent with the result of Watkins,23 but not consistent with that of Nolen-Hoeksema et al27 Another study showed that some characteristics including the severity of depression were not different between genders 28,29. So the coping and ruminative style by gender needs further research.…”
Section: Discussionsupporting
confidence: 71%
“…The gender difference of the original RRS was not apparent in our data. This is consistent with the result of Watkins,23 but not consistent with that of Nolen-Hoeksema et al27 Another study showed that some characteristics including the severity of depression were not different between genders 28,29. So the coping and ruminative style by gender needs further research.…”
Section: Discussionsupporting
confidence: 71%
“…These data have been presented in detail elsewhere [15] . In short, among the 607 patients who did not accept to participate in the face-to-face interview, 238 patients alternatively participated in a telephone interview or returned a brief questionnaire.…”
Section: Participants Versus Non-participantsmentioning
confidence: 99%
“…Consistent with this, several studies have suggested that even in 'pure' depression, women report more symptoms of anxiety. In a cohort of first episode patients with major depression, Bukh, Bock, Vinberg, Gether, and Kessing (2010) reported that women presented with more symptoms of anxiety and have higher scores for harm avoidance than men.…”
Section: Co-morbid Anxietymentioning
confidence: 99%